Metastatic Malignant Melanoma of the Inguinal Lymph Node with Unknown Primary Lesion - Sherif Ali Eltawansy; Ryane Panasiti; Samaa Hasanien; Dennis Lourdusamy; David Sharon (Case Reports in Medicine)
Background. Malignant melanoma could present with metastasis with unknown primary (MUP) and this happens in 2-3% according to the studies. Around 90% of melanomas have cutaneous origin, but still there are melanomas that could be found in visceral organs or lymph nodes with unknown primary site. Spontaneous regression of the primary site could be an explanation. Case Report. We report a 58-year-old Caucasian male who presented with a right sided swelling in the inguinal region. Surgery was performed and biopsy showed metastatic malignant melanoma. No cutaneous lesions were identified by history or physical examination. Work up could not detect the primary lesion and patient was started on radiotherapy and immunotherapy. Conclusion. We present a case of malignant melanoma of unknown primary presenting in an unusual place which is the inguinal lymph node. Theories try to explain the pathway of development of such tumors and one of the theories mentions that it could be a spontaneous regression of the primary cutaneous lesion. Another theory is that it could be from transformation of aberrant melanocyte within the lymph node. Prognosis is postulated to be better in this case than in melanoma with a known primary.